In Vitro Transcription as a Strategy to Enhance Mesenchymal Stem Cell Secretome for Therapeutic Use: An Overview - Nugraha, Dendi Krisna; Falah, Ariq (International Journal of Cell and Biomedical Science, 2024)
Mesenchymal stem cells (MSCs) have become a cornerstone of regenerative medicine owing to their capacity to secrete a diverse array of bioactive molecules, collectively termed the secretome. The MSC secretome exerts profound immunomodulatory, anti-inflammatory, and trophic effects that underpin much of the therapeutic efficacy observed in MSC-based interventions. Nevertheless, variability in the secretory profile across donors, tissue sources, and culture conditions continues to limit the reproducibility and potency of MSC-derived therapies. Recent advancements in in vitro transcription (IVT) mRNA technology have emerged as a robust and transient platform for the reprogramming of mesenchymal stem cells (MSCs) without the need for genomic integration. Through the use of IVT-mRNA-mediated expression of selected cytokines, growth factors, or homing receptors, MSCs can be endowed with enhanced anti-inflammatory and regenerative capabilities while preserving their native phenotype and viability. This review summarizes current IVT-mRNA–based strategies for engineering the MSC secretome, with an emphasis on augmenting anti-inflammatory cytokines (e.g., IL-10, TSG-6) and growth factors (e.g., VEGF, HGF, FGF2). The review also examines how IVT-mRNA redefines the cellular secretory landscape, outlines key considerations in IVT-mRNA design and optimization, and discusses translational implications for both cell-based and cell-free therapeutic applications. Finally, it underscores persistent challenges, including transient transgene expression, innate immune activation, and delivery inefficiency, and contemplates future prospects for integrating IVT-mRNA technology with advanced biomaterials, cellular priming methodologies, and multifactorial modulation to achieve consistent and potent therapeutic secretomes.